Simultaneous Physico-Mechanical and In Vivo Assessment towards Factual Skin Performance Profile of Topical Polymeric Film-Forming Systems - Mirjana D. Timotijević; Tanja Ilić; Snežana Savić; Ivana Pantelić (MDPI AG, 2022)
Topical film-forming systems (FFS) change drastically after solvent displacement, therefore indicating their skin metamorphosis/transformation as a property of special regulatory and research interest. This paper deals with the lack of suitable characterization techniques, suggesting a set of methods able to provide a comprehensive notion of FFS skin performance. After screening the physico-chemical, mechanical and sensory properties of FFS and resulting films, an elaborate three-phase in vivo study was performed, covering skin irritation, friction and substantivity. Upon removal of 24-hour occlusion, no significant change in erythema index was observed, while the film-former type (cellulose ether, acrylate and/or vinyl polymer) affected transepidermal water loss (TEWL); hydrophobic methacrylate copolymer-based samples decreased TEWL by 40-50%, suggesting a semi-occlusive effect. Although both the tribological parameters related to the friction coefficient and the friction curve's plateau provided valuable data, their analysis indicated the importance of the moment the plateau is reached as the onset of the secondary formulation, while the tertiary state is still best described by the completion of the film's drying time. The final part of the in vivo study proved the high in-use substantivity of all samples but confirmed the optimal 4:1 ratio of hydrophobic cationic and hydrophilic polymers, as indicated during early physico-mechanical screening.